USER-CENTRIC WEB-BASED LOCATION NAVIGATION SYSTEM FOR BABCOCK UNIVERSITY - Oladipo, Sunday Oluwadare; Kuyoro, Afolashade; Eweoya, Ibukun; Amanze, Ruth Chinkata; Fatade, Oluwayemisi Boye; Akinwunmi, Damilare Samuel; Idepefo, Felix (FUDMA Journal of Sciences, 2026)
Purpose driven movement is a paramount characteristic of living things. People, however, often face challenges with navigation especially in unfamiliar terrane which can lead to frustration, anxiety, loss of valuable time, lateness and more. This is of immense consequence especially in an academic environment. Hence, there arises the need for a campus navigation system. The campus navigation system therefore is built as a comprehensive, user-centric solution for seamless navigation and combines interactive mapping, categorized location access, and visual previews, which enhances user experience and accessibility for students, visitors, and parents altogether.